Antifungal activity of cyclopaldic acid from Antarctic Penicillium against phytopathogenic fungi - Vieira, Gabrielle [UNESP]; Sette, Lara Durães [UNESP]; de Angelis, Derlene Attili; Sass, Daiane Cristina [UNESP] (Springer Nature, 2023)
Plant pathogens cause great economic losses in agriculture. To reduce damage, chemical pesticides have been frequently used, but these compounds in addition to causing risks to the environment and health, its continuous use has given rise to resistant phytopathogens, threatening the efficiency of control methods. One alternative for such a problem is the use of natural products with high antifungal activity and low toxicity. Here, we present the production, isolation, and identification of cyclopaldic acid, a bioactive compound produced by Penicillium sp. CRM 1540, a fungal strain isolated from Antarctic marine sediment. The crude extract was fractionated by reversed-phase chromatography and yielded 40 fractions, from which fraction F17 was selected. We used 1D and 2D Nuclear Magnetic Resonance analysis in DMSO-d6 and CDCl3, together with mass spectrometry, to identify the compound as cyclopaldic acid C11H10O6 (238 Da). The pure compound was evaluated for antimicrobial activity against phytopathogenic fungi of global agricultural importance, namely: Macrophomina phaseolina, Rhizoctonia solani, and Sclerotinia sclerotiorum. The antifungal assay revealed the potential of cyclopaldic acid, produced by Penicillium sp. CRM 1540, as a leading molecule against M. phaseolina and R. solani, with more than 90% of growth inhibition after 96h of contact with the fungal cells using 100 µg mL−1, and more than 70% using 50 µg mL−1.
Keywords: Cyclopaldic acid; Macrophomina phaseolina; Penicillium; Rhizoctonia solani; Sclerotinia sclerotiorum